Automated Home Appliances Control using Embedded Web Server - Abdul Ahad; Y. Mahesh; G. Sukanya; N. Harika; A. Uma Sri (Universitas Islam Sultan Agung, 2014)
In modern construction in industrialized nations, most homes have been wired for TV, lights and fans etc... Many household tasks were automated by the development of specialized automated appliances. In this project we are going to create the embedded web server so that we can control the electrical devices through online by using either computer or by using smart phone. The purpose of this project is to design a control system that able to control a system device remotely from distance and monitoring condition of the system in real-time as well. This project shows how to set up an Arduino with Ethernet shield as a web server. The web servers in this Project are used to serve up web pages that can be accessed from a web browser and allows our hardware to be controlled from web browser. Starting from basic, our example for this project is simple. We want to access our device by switching ON-OFF LED and monitor analog input data acquisition from web server, which are the computer and Arduino connected to the same network.